Inter-Professional Collaboration as the Main Cooperation Trend in the International Forensic Community - A. I. Usov (Теория и практика судебной экспертизы)
The paper reflects on the outcomes of the most recent conference of the International Association of Forensic Sciences (IAFS) held in Toronto, Canada. The meeting of delegates from all continents was organized around the theme «Inter-Professional Collaboration in Forensic Science», with the aim of exploring forensic scientists' responses to the challenges of the modern world. The meeting outcomes are analyzed in terms of valuable insights for the development of forensic practicesin Russia through the strengthening of multidisciplinary methodological approaches